Pengembangan Aplikasi Perangkat Bergerak Panduan dan Resep Masakan untuk Mahasiswa berbasis Android - Muhammad Ziyad Al Maududi; Agi Putra Kharisma; Fais Al Huda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Cooking is a process of creating a food by following the steps in sequence. Based on a survey conducted on 82 students of the Faculty of Computer Science, Universitas Brawijaya, it was found that 86.6 percent of respondents had faced problems when cooking related to ingredients and seasonings, recipes, level of maturity, cooking methods, cooking time, dosage, determining the menu, and the results obtained not as expected. 96.3 percent of respondents feel they will be helped in overcoming problems related to cooking with an application that provides recipes. Several recipe applications have been developed, but none are specifically for students, where the recipes are practical and simple with easily available ingredients. Therefore, an application for guides and recipes was developed for students. The application was developed using SDLC Prototyping, Kotlin programming language, Firebase as data storage, with MVVM architecture. Applications are tested using black box testing, and usability testing. In black box testing, the success rate is 100%. In usability testing, the effectiveness level is 100%, and in SUS, the value is 85.5, which means the application can be accepted by the user.